THE DIFFICULTIES OF INDONESIAN STUDENTS IN LEARNING ENGLISH PLURAL FORM: CONTRASTIVE ANALYSIS - Komang Trisnadewi (Yavana Bhasha : Journal of English Language Education, 2019)
A comparative analysis is needed between the two languages or known ascontrastive analysis to identify their structural similarities and differences so thatthe material and methods of teaching will be appropriate. Further than that, thispaper is aimed to give a clear understanding about how Indonesian differs fromEnglish in the sense of its language features, especially in plural form. It is knownthat the structure of the plural between English and Indonesian is differentalthough some similarities were found. Indonesian learners will find it difficult tolearn plural words because in terms of word formation, English and Indonesian arevery different. The formation of plural words in English is through the process ofaffixation, while in Indonesian, the formation of plural is through reduplication andaddition of quantifier and number. It is necessary to give more explanations andexercises to learn the plural of English because with a lot of practice, it is hoped thatIndonesian learners will start to get used to the formation of the plurals.